Preparation of Chitosan/β-Cyclodextrin and Its Absorption on Puerarin - Lin, Qiang; Huo, Qing; Su, Miao; Wang, Lili (Asian Journal of Chemistry, 2012)
A new type of chitosan/b-cyclodextrin was prepared by reversed-phase suspension method with the chitosan and b-cyclodextrin as materials, sodium periodate as oxidant, epichlorohydrin as crosslinking agent in inverse suspension. Its absorption behaviour for puerarin was studied. The structure was characterized by means of IR and SEM. The different affected factors on absorption of puerarin were investigated. Results showed that the adsorption content was optimal when the adsorption time was 4 h, the temperature was 35 ºC, pH = 7 and initial concentration of puerarin was 0.5 mg/mL. The absorptive capability of chitosan/b-cyclodextrin for pueratin was 52.43 mg/g.